Clinical cost evaluation and health benefits of post‐bariatric intervention for patients with type 2 diabetes living in the UK. Issue 6 (27th September 2021) - Alkharaiji, Mohammed; Anyanwagu, Uchenna; Crabtree, Thomas; Gordon, Jason; Idris, Iskandar
Summary: To assess associated healthcare costs and risk of developing obesity‐related comorbidities among patients with type 2 diabetes with severe obesity and receiving insulin treatment, following bariatric surgery (BS). A retrospective cohort study was conducted from a UK electronic primary care database. Propensity score matching (1:1) was performed for BS with non‐BS cohort. Follow‐up was over 5 years (694 person‐years), comparing drug utilization with clinical cost differences, such as visits to General practitioners (GPs), hospitalization, and laboratory use. Cox proportional regression was used to compute differences in the risk of obesity‐related comorbidities and chi‐square analysis to explore differences in insulin independency and diabetes remission proportions during follow‐up. Eighty patients who received BS were matched to 80 non‐BS ( N = 160). The baseline mean age was 48.3 years (SD: 12.9) (61% female), and body mass index was 39.3 kg/m 2 (SD: 9.3). During follow‐up, antidiabetic drug cost was significantly lower in the BS group than in the non‐BS (median cost/person [£]: 527.77 [interquartile range (IQR): 1196.11] vs. 1564.13 [IQR: 1576.01]; p < 0.001). Overall, aggregate cost analysis showed a significant total healthcare cost reduction in the BS group (median cost/person [£]: 1597.96 [IQR: 2631.84] vs. 2440.12 [IQR: 2242.95]; p = 0.050). BS significantly protected against obesity‐related comorbidities compared with the non‐BS (adjusted hazard ratio: 0.56; 95% confidence interval: 0.32–0.96; p = 0.036) and increased insulin independency throughout all follow‐up points: at year 5: 48.1% versus 28.9%; p = 0.044, respectively. While BS shows evidence of cost efficiency, cost saving was not identified. The efficiency is evident by the protective effect against crude obesity‐related comorbidities associated with increased insulin independency.